A SURVEY ON THE PERCEPTIONS OF CO-OPERATORS ON GENDER DISPARITY AND FINANCIAL VIABILITY OF AGRICULTURAL COOPERATIVE SOCIETIES IN RIVERS STATE, NIGERIA. Issue 3 (2017) - Uche, C; Onyegbula, F I; Ajie, E N
No abstract available